Femtosecond near-infrared lasers as a novel tool for non-invasive real-time high-resolution time-lapse imaging of chloroplast division in living bundle sheath cells of Arabidopsis. - Tirlapur, U; König, K (2001)
Non-linear excitation of fluorophores by contemporaneous absorption of two or more near-infrared (NIR) photons following diffraction-limited focusing with high-numerical-aperture objectives circumvents out-of-focus fluorescence (without a confocal pinhole) and spatially limits photobleaching and photodamage to the minute sub-femtoliter focal volume. This is in contrast to optical events in conventional confocal imaging systems using ultraviolet (UV) or visible laser sources wherein the entire sectors of the specimen above and below the plane of focus experience massive photostress and photodamage. In addition, NIR wavelengths penetrate deeper into the highly scattering environs of plant tissue than UV and visible wavelengths. We delineate a novel non-invasive technique using NIR femtosecond laser pulses at lambda = 740, 760, 780, and 800 nm for induction of chlorophyll fluorescence by the two-photon effect as well as for intra-tissue time-lapse vital three-dimensional imaging of fundamental events of chloroplast division in deeply seated bundle sheath cells of Arabidopsis thaliana (L.) Heynh. leaves. Our findings establish that (i) mature bundle sheath chloroplasts are indeed capable of division, (ii) the dividing chloroplasts assume a distinct constricted/dumbbell-shaped profile with an average lifespan of 20-25 min, (iii) the complete division of the pre-existing chloroplasts occurs within 50 min, and (iv) the two derivative daughter chloroplasts are invariably unequal in size. This novel NIR-laser-based technique has any number of potential applications, including (i) non-invasive intra-vital imaging of molecular and ion dynamics, (ii) non-destructive screening of mutants impaired in photosynthesis, (iii) diagnosis of physiological states of plants and (iv) bio-optical taxonomy.